Daughter of Eden : [large type] [large type] Eve's story - Smith, Jill Eileen, 1958- (Smith, Jill Eileen, 1958- Daughters of the promised land., 2023)
"The first time she opens her eyes, Eve gazes on One whose beauty nearly blinds her, whose breath is in her lungs. Her Creator takes her hand and gives her to one like her and yet different. Together, she and Adam experience pure joy as they explore Eden. But her favorite moments are when the Creator comes to walk with them, day after day.Until everything changes. With one act of disobedience, Eve finds that her world is no longer a friendly place. With remorse in her heart, she must face the unknown future--the births, the deaths, the sacrifices, the loss of the one home she has ever known. Perhaps worst of all is the loss of trust, not only with her Creator but with the man who shares her life. How will they ever survive out of Eden?Bestselling biblical fiction author Jill Eileen Smith imagines the life of the first woman to ever live, unspooling a story of love, loss, and the promise of redemption"--